Maximizing Polysaccharides and Phycoerythrin in Porphyridium purpureum via the Addition of Exogenous Compounds: A Response-Surface-Methodology Approach - Sanjiong Yi; Ai-Hua Zhang; Jianke Huang; Ting Yao; Bo Feng; Xinghu Zhou; Yadong Hu; Mingxuan Pan (Marine Drugs, 2024)
Phycoerythrin and polysaccharides have significant commercial value in medicine, cosmetics, and food industries due to their excellent bioactive functions. To maximize the production of biomass, phycoerythrin, and polysaccharides in Porphyridium purpureum, culture media were supplemented with calcium gluconate (CG), magnesium gluconate (MG) and polypeptides (BT), and their optimal amounts were determined using the response surface methodology (RSM) based on three single-factor experiments. The optimal concentrations of CG, MG, and BT were determined to be 4, 12, and 2 g L−1, respectively. The RSM-based models indicated that biomass and phycoerythrin production were significantly affected only by MG and BT, respectively. However, polysaccharide production was significantly affected by the interactions between CG and BT and those between MG and BT, with no significant effect from BT alone. Using the optimized culture conditions, the maximum biomass (5.97 g L−1), phycoerythrin (102.95 mg L−1), and polysaccharide (1.42 g L−1) concentrations met and even surpassed the model-predicted maximums. After optimization, biomass, phycoerythrin, and polysaccharides concentrations increased by 132.3%, 27.97%, and 136.67%, respectively, compared to the control. Overall, this study establishes a strong foundation for the highly efficient production of phycoerythrin and polysaccharides using P. purpureum.